Cash holdings of German open-end equity funds: Does ownership matter? - Niko Dötz; Mark Weth (Deutsche Bundesbank, 2013)
In the light of the recent financial crisis, the discussion on the nature of runs and on the stabilizing role of liquidity holdings has intensified. This paper explores the cash management conducted by German open-end equity funds for the period between 2005 and 2010. Since ownership structures may have important consequences according to recent work, we distinguish funds whose shares are predominantly held by retail investors from funds with a stronger institutional orientation. Conditional on poor portfolio liquidity, we find that managers of permanently retail-oriented funds tend to move towards higher cash-to-asset positions. Cashbuilding intensities are found to be lower when illiquid funds are institutional-oriented or when the portfolio liquidity of retail-based funds is higher. The striking effort undertaken by poorly liquid funds with a lasting retail-orientation is likely to be linked to their exposure to the risk of strategic investor behavior at times of distress. We conclude that conditional on their liquidity status, these funds use cash as a device to provide for the ownership-related fragility of their funding base, thereby contributing to the self-stabilization of the financial system.
Keywords: G01; G11; G23; G32; 330; cash holdings; equity funds; ownership; strategic complementarities; financial crisis